Differential Reaction of Hosts, Gene Characterization and Management of Huanglongbing Using Chemical Treatments - Shokrollah, Haji Vand (2010)
Citrus is an important crop worldwide and the total production of citrus was about 105.4 million tons in 2006. Unfortunately many diseases have been threatening citrus. The disorder of citrus described as Huanglongbing (HLB) which is known as citrus greening disease is caused by the fastidious phloem limited bacterium in the genus Candidatus Liberibacter and caused severe damage on citrus in more than forty countries including Malaysia. Although HLB has been detected in citrus in Malaysia, there have been few reported studies in the country. Study on screening the local and non-local Citrus species in Malaysia would be useful to select the best rootstocks and interstocks against the HLB causing greening disease in Citrus species. There is also very little information on seed transmission of HLB disease,pathogen movement and the good agriculture practices there can control and reduce greening disease severity of citrus. Seeds were collected from infected trees and germinated in a screenhouse condition. New leaves were collected two months after germination for detection of the HLB using conventional PCR. HLB was not detected in the seed and HLB is not a seed borne disease. The healthy Citrus reticulata (Limau madu) seedlings were used to detect the HLB pathogen movement. They were inoculated using grafting method and the HLB movement evaluated using PCR test after two months. HLB can reach to the roots system twenty six weeks after inoculation. This means that resistant or tolerant rootstocks maybe effective to control or to reduce the severity of HLB because rootstocks provide the root system for the scion. Screening of eighteen Citrus species for susceptibility to HLB was carried out through grafting. C. reticulata that showed typical symptoms of HLB was identified and confirmed by PCR test and used as a source of inoculums. Infected Citrus species showed low total biomass, plant heightand stem diameter when compared to non-inoculated Citrus species. The C.reticulata, C. sinensis, and C. microcarpa showed lowest total biomass, plant height and stem diameter. HLB was detected on 15 species by PCR test, and the species were categorized into three groups; severe group from 58 to 80% severity, includes C. reticulata, C. sinensis, C. reshni (cleopatra), moderate group from 41 to 50% severity, includes Furtunella spp. (Kasturi Chini), C. macrophylla, C. microcarpa (Kasturi), mild group from 17 to 25% severity, includes C.medica, C. aurantifolia (Limau nipis), Citrus sp. (Limau naga), C. jambhiri and three Citrus sp. (Sr.No. 12,15 and 16). HLB was detected in C. aurantium and C. aurantifolia by conventional PCR test (16% PCR test and without symptoms). Effects of rootstocks and interstocks against HLB disease were studied. The tolerant and resistant species were chosen for rootstocks and interstocks and evaluated using conventional and nested PCR. HLB symptom was not observed when C. grandis used as a rootstock and C. hystrix used as an interstock and vice versa with C. reticulata as the scion. In this combination, dry matter, plant height and stem diameter also were significantly increased compared to combination with C.aurantium and C. aurantifolia. High percentage of disease severity was measured in combination between C. aurantum rootstock and C. aurantifolia interstock. Ca. Liberibacter asiaticus was detected in all combinations using nested PCR. Effects of chemical treatments on HLB infected C. reticulata orchard were conducted in Kuala Terengganu. The results showed a significant difference among the treatments. Fruit quantity and quality were significantly increased on treatments T4 (antibiotic + GA3), T7 (antibiotic + GA3 + foliar fertilizer) and T5 (antibiotic + foliar fertilizer) compared to fruit quantity and quality of T8 (control). Total thickness of cell wall also were significantly increased on T4, T7, T5 and T6 (GA3 + foliar fertilizer) compared to T8 (control), T3 (foliar fertilizer), T2 (GA3) and T1 (antibiotic). HLB bacteria were successfully detected using nested-PCR on all treatments. Spherical and rod shape of Ca. Liberibacter asiaticus bacteria were detected in sieve tube cells of phloem. Cross section of sieve tube showed abundant bacteria on the cells and it damaged cell wall and middle lamella. A new strain of HLB was successfully obtained and registered (GU133055) in NCBI gene bank as new strain of HLB from C. reticulata in Terengganu,Malaysia.